(3GdcTa hGdHjGf aj JaSjQ GdbQBfs - (3CHh ESMGb CMeO Hf eMeO Hf EHQGgje GdfjSGHhQj, GdKYdHj,J (B427 (3g` s
(3ChdgG (B:s
(3Chd ShQI (B"(3jhSa(B" s
(3BNQgG (B:s
(3BNQ ShQI (B"(3Gdcga(B" s
(3GdfSNI HgG MhGTs
(3LRA efgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B212s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B38 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1488s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs